Uma crítica às relações de consumo colaborativo em mercados emergentes: um estudo com usuários da Uber - Argentino Netto, Vicente (2019)
The purpose of this dissertation is to analyze the perceptions of Uber users, based on complaints about their service provision, registered on Reclame Aqui online platform, to identify the main causes that generate negative impacts on this relationship. The study has as theoretical base a review of the literature about the sharing economy, elaborated from the references of critical perspectives to the business model used by the company. Qualitative research is used in this investigation, using the technique of content analysis on a sample of complaints, with the premise of not only explicitly extracting what has been said, also obtaining more inductive and subjective meanings through inference and interpretation of users' messages. The result of the analysis allows us to make three propositions that point to specific causes that generate negative impacts on the relations between the parties. The first indicates the excessive delegation of processes by Uber to users and drivers, within a standardized and inflexible scheme. The second shows the strong control and monitoring pressure exerted on the driver that reduces his commitment and the third shows the algorithmic relationship management, with automated and simplified decision-making. All causes are due to overuse of technology, such as process automation, algorithm decisions, standardization of procedures and dehumanization of relationships